Pengaruh Media Sosial Instagram terhadap Pemanfaatan Perpustakaan pada Suku Dinas Perpustakaan Dan Kearsipan Jakarta Utara - Septianti, Adinda Triani; Wicaksono, Hendra; Erza, Elfitri Kurnia (Institut Agama Islam Negeri Salatiga, 2023)
Technological developments provide convenience quickly to its users, one of the media for technological and communication developments is Instagram social media. Instagram social media makes it easy to find and get information. This means that libraries need to keep up with the times. Libraries are required in order to introduce and utilize various collections, services and activities provided for the community. The North Jakarta sub-district library has social media Instagram @perpusjkt_utara to disseminate information, services, collections and activities in the library. The research aims to find out how social media and Instagram influences the use of libraries in the North Jakarta Library and archives department. The method used in this research is a correlational quantitative method to determine the influence of Instagram social media on library use with a total of 76 library user respondents. The results obtained in this research show that the Instagram social media @perpusjkt_utara with all the activities carried out encourages library users to utilize the library in terms of services, activity events and the existence of collections so that the Instagram social media variable has a significant effect on library utilization with a significance value of 0.000 0, 05 and the Pearson correlations obtained were 0.863 in the interval 0.80 - 1.000, there was a positive and strong correlation. The research concludes that the social media Instagram @perpusjkt_utara with all the activities carried out encourages library users to utilize the library in terms of services, event activities, and the existence of collections. So the social media variable Instagram has a significant effect on library utilization.